Method for producing curable composition

JP2025029911APending Publication Date: 2025-03-07KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023134800
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0007】 本発明の一態様によれば、表面タックが軽減され、機械強度に優れた硬化物を与える硬化性組成物の製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029911000001
    Figure 2025029911000001
  • Figure 2025029911000002
    Figure 2025029911000002
Patent Text Reader

Abstract

To provide a method for producing a curable composition that yields a cured product with reduced surface tack and excellent mechanical strength.SOLUTION: A method for producing a curable composition according to one embodiment of the present invention includes the following steps (1) to (3): (1) a step of mixing (A) a (meth)acrylic copolymer having an alkoxysilyl group with (B) an oxygen-curable substance; (2) a step of adding (C) an amine to the mixture prepared in the step (1); and (3) a step of adding (D) a curing catalyst to the mixture obtained in the step (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a curable composition. [Background technology]

[0002] Polymer molecules having alkoxysilyl groups form siloxane bonds with other polymer molecules as a result of hydrolysis of the alkoxysilyl groups. This crosslinking reaction produces a rubber-like cured product. Curable compositions containing such polymer molecules are used in sealing materials, adhesives, paints, etc. (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2022-049666 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional curable compositions have room for improvement in terms of surface tackiness and mechanical strength of the resulting cured products.

[0005] An object of one aspect of the present invention is to provide a method for producing a curable composition that gives a cured product having reduced surface tack and excellent mechanical strength. [Means for solving the problem]

[0006] A method for producing a curable composition according to one embodiment of the present invention includes the following steps (1) to (3): Step (1): (A) mixing a (meth)acrylic copolymer having an alkoxysilyl group with (B) an oxygen-curable substance; Step (2): adding an amine (C) to the mixture obtained in step (1); Step (3): adding a curing catalyst (D) to the mixture obtained in step (2); The (A) (meth)acrylic copolymer having an alkoxysilyl group has a molecular weight distribution (Mw / Mn) of 1.8 or less, The (A) (meth)acrylic copolymer having an alkoxysilyl group has an XY diblock structure having an X block and a Y block or an XYX triblock structure in the molecule, The number of repeating units derived from a (meth)acrylic ester monomer having an alkoxysilyl group contained in the X block is on average more than 2.0 per molecule of the (A) (meth)acrylic copolymer having an alkoxysilyl group, and the number of repeating units derived from a (meth)acrylic ester monomer having an alkoxysilyl group contained in the Y block is 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block. Effect of the Invention

[0007] According to one aspect of the present invention, there is provided a method for producing a curable composition which gives a cured product having reduced surface tack and excellent mechanical strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described in detail, but the present invention is not limited to this embodiment.

[0009] Unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more and B or less." In this specification, "(meth)acrylic" means "acrylic and / or methacrylic."

[0010] 1. Method for Producing Curable Composition and Cured Product A method for producing a curable composition according to one embodiment of the present invention includes the following steps (1) to (3). Step (1): A step of mixing (A) an alkoxysilyl group-containing (meth)acrylic copolymer and (B) an oxygen-curable substance. Step (2): Adding an amine (C) to the mixture obtained in step (1). Step (3): Adding a curing catalyst (D) to the mixture obtained in step (2).

[0011] In step (1), (E) a polyoxyalkylene polymer having a silyl group may be further mixed. In this case, the order of mixing (A) the (meth)acrylic copolymer having an alkoxysilyl group, (B) the oxygen curing substance, and (E) the polyoxyalkylene polymer having a silyl group in step (1) is not particularly limited. Each component may be mixed in any order, or all components may be mixed at once. Preferably, (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group are mixed, and then (B) the oxygen curing substance is further added and mixed.

[0012] In the past, when producing a curable composition, (C) the amine and (D) the curing catalyst were already mixed and then mixed with (A) the (meth)acrylic copolymer having an alkoxysilyl group. For example, (A) the (meth)acrylic copolymer having an alkoxysilyl group, (C) the amine and (D) the curing catalyst were mixed simultaneously, or a mixture of (C) the amine and (D) the curing catalyst was added to (A) the (meth)acrylic copolymer having an alkoxysilyl group and mixed.

[0013] However, the present inventors have found that by first mixing a mixture containing (A) a (meth)acrylic copolymer having an alkoxysilyl group and (B) an oxygen-curable substance with (C) an amine, and then further adding and mixing (D) a curing catalyst, a cured product with reduced surface tackiness can be obtained.

[0014] A cured product is obtained by curing the curable composition obtained by the above-mentioned manufacturing method. For example, the curable composition can absorb ambient moisture and spontaneously change into a cured product by the above-mentioned manufacturing method. The use of the cured product is not particularly limited. Examples include architectural and industrial sealants, electrical and electronic component materials (such as solar cell back sealants), electrical insulating materials (such as insulating coating materials for wires and cables), pressure sensitive adhesives, adhesives, elastic adhesives, contact adhesives, tile adhesives, paints, coating materials, sealing materials for can lids, etc., potting agents for electrical and electronic use, films, gaskets, casting materials, various molding materials, artificial marble, rust-proofing and waterproofing sealants for cut parts of wire-reinforced glass or laminated glass, and waterproofing agents.

[0015] In one embodiment, the cured product is in the form of a film. Therefore, the present invention also includes a method for producing a film, which comprises the step of preparing a curable composition by the above-mentioned production method. The lower limit of the thickness of the produced film can be 0.1 mm or more, 0.5 mm or more, 1 mm or more, 5 mm or more, or 10 mm or more. The upper limit of the thickness of the produced film can be 100 mm or less, 90 mm or less, 80 mm or less, 70 mm or less, 60 mm or less, or 50 mm or less.

[0016] The film-like cured product can be produced, for example, by applying the curable composition to a substrate and then curing it. The film may be used in a state where it is peeled off from the substrate, or in a state where the substrate and the film are integrated. Examples of applications of the film-like cured product include sealing materials, coating agents, and adhesives.

[0017] 2. Components contained in the curable composition The components contained in the curable composition, including optional components, will be described below.

[0018] [2.1. (A) (Meth)acrylic copolymer] [2.1.1. Structure of (meth)acrylic copolymer] The (meth)acrylic copolymer has an X block and a Y block, and contains an XY diblock structure or an XYX triblock structure in the molecule. The structure of the entire molecule of the (meth)acrylic copolymer is not particularly limited as long as it contains an XY diblock structure or an XYX triblock structure, and may be, for example, an XYXY tetrablock structure.

[0019] Here, the term "XYX triblock structure" refers to what is generally known by those skilled in the art as an "ABA triblock structure." The ratio of X / Y in the (meth)acrylic copolymer is preferably from (5 / 95) to (60 / 40), more preferably from (15 / 85) to (40 / 60).

[0020] In one embodiment, the (meth)acrylic copolymer molecule has an XY diblock structure. In the molecule of the XY diblock structure, the X block can be a region of 40% or less, 30% or less, or 25% or less from one end of the molecule (all repeating units contained in the molecule are taken as 100%). Here, the X block is the block on the side where alkoxysilyl groups are distributed in a relatively large amount.

[0021] In one embodiment, the (meth)acrylic copolymer molecule has an XYX triblock structure. In the XYX triblock structure molecule, the X block can be 40% or less, 30% or less, or 25% or less of the region from the end of the molecule (all repeating units contained in the molecule are taken as 100%). Here, the X block is a block located at both ends of the molecule.

[0022] The (meth)acrylic copolymer has a repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group. The repeating unit derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group is contained relatively in large amounts in the X block. The repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block are more than 2.0 on average per molecule of the (meth)acrylic copolymer. When the (meth)acrylic copolymer has two or more X blocks in one molecule, the total number of repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the multiple X blocks is more than 2.0 on average. On the other hand, the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block are 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block.

[0023] The repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block are on average more than 2.0 per molecule of the (meth)acrylic copolymer, preferably 2.1 or more, more preferably 2.2 or more, even more preferably 2.3 or more, and particularly preferably 2.5 or more. Similarly, the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block are preferably 0.5% by weight or more, more preferably 2.0% by weight or more, and even more preferably 3.0% by weight or more based on the weight of all repeating units contained in the X block.

[0024] The upper limit of the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is preferably 90% by weight or less, more preferably 60% by weight or less, and even more preferably 30% by weight or less. The upper limit of the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is less than 5% by weight, preferably 4% by weight or less, more preferably 3% by weight or less, even more preferably 2% by weight or less, and particularly preferably 1% by weight or less, based on the weight of all repeating units contained in the Y block. The lower limit of the repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is preferably 0% by weight or more, and more preferably more than 0% by weight, based on the weight of all repeating units contained in the Y block.

[0025] Specific examples of (meth)acrylic acid ester monomers having an alkoxysilyl group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0026] The (meth)acrylic copolymer may contain a repeating unit derived from a (meth)acrylic monomer having a long side chain. In this specification, the "(meth)acrylic monomer having a long side chain" refers to a repeating unit derived from a (meth)acrylic monomer having a long side chain, represented by the formula: R 1 CH=CHCOOR 2 In the formula, R 1 R is a hydrogen atom or a methyl group. 2 is a group having 9 or more carbon atoms.

[0027] The content of the repeating unit derived from the (meth)acrylic monomer having a long side chain is preferably 1% by weight or more of the total constitutional units contained in the (meth)acrylic copolymer. The (meth)acrylic copolymer containing such a repeating unit may have improved compatibility with the polyoxyalkylene polymer, or the physical properties of the resulting cured product may be improved. The upper limit of the content of the repeating unit derived from the (meth)acrylic monomer having a long side chain is preferably 5% by weight or less, more preferably 3% by weight or less, and even more preferably 1% by weight or less. If the content is within the above range, the production cost of the (meth)acrylic copolymer does not rise excessively.

[0028] Examples of (meth)acrylic monomers having a long side chain include nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, icosyl (meth)acrylate, docosyl (meth)acrylate, oleyl (meth)acrylate, linoleyl (meth)acrylate, and isobornyl (meth)acrylate.

[0029] Among the above-mentioned monomers, one or more selected from octadecyl (meth)acrylate, oleyl (meth)acrylate, and linoleyl (meth)acrylate are preferred. These monomers have the advantage of being liquid at room temperature and having high polymerization stability. In addition, by blending these monomers, a (meth)acrylic acid copolymer having high compatibility with a polyoxyalkylene polymer can be obtained.

[0030] In this specification, the term "(meth)acrylic monomer having a non-long side chain" refers to a (meth)acrylic monomer having a non-long side chain in the above formula, R 2represents a monomer having 8 or less carbon atoms. Examples of such monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, isopropoxyethyl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, glycidyl (meth)acrylate, 1-ethylcyclopentyl ether (meth)acrylate, and dimethylaminoethyl (meth)acrylate.

[0031] Among the above-mentioned monomers, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred. These monomers have low procurement costs and are suitable for the purpose of reducing the production costs of the (meth)acrylic copolymer.

[0032] Furthermore, from the viewpoint of glass transition point, one or more selected from n-butyl acrylate and 2-ethylhexyl acrylate are preferred. The (meth)acrylic copolymer obtained from these monomers has a low glass transition point and a low polymer viscosity. Therefore, a curable composition that is easy to use in a low temperature environment can be obtained.

[0033] [2.1.2. Alkoxysilyl groups in (meth)acrylic copolymers] The (meth)acrylic copolymer has an alkoxysilyl group. The alkoxysilyl group of the (meth)acrylic copolymer may be derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group. In one embodiment, the alkoxysilyl group is represented by the following general formula: -[Si(R 4 ) 2-b (Y) b O] m -Si(R 5 ) 3-a (Y) a

[0034] In the formula, R 4 and R 5 are independently an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, a methoxymethyl group, or (R') 3 R' is a triorganosiloxy group represented by SiO-. R' is a monovalent hydrocarbon group having 1 to 20 carbon atoms. The three R's may be the same or different. R 4 or R 5 When two or more are present, they may be the same or different. Y is an alkoxy group having 1 to 20 carbon atoms. When two or more Y are present, they may be the same or different. a is 0, 1, 2 or 3. b is 0, 1 or 2. m is an integer of 0 to 19, provided that the relationship a+mb≧1 is satisfied.

[0035] Generally, the fewer the carbon atoms in an alkoxy group, the higher its reactivity. In other words, the reactivity decreases in the order of methoxy group, ethoxy group, propoxy group, etc. Therefore, an appropriate alkoxy group can be selected depending on the production method and application of component (A).

[0036] The specific structure of the (meth)acrylic acid ester monomer having an alkoxysilyl group is not particularly limited. An example is a monomer represented by the following general formula: H 2 C=CR 6 C(=O)O-(CH 2 )m -SiR 7 n (OR 8 ) 3-n

[0037] In the formula, R 6 is hydrogen or a methyl group. 7 and R 8 R is at least one selected from the group consisting of hydrogen, a methyl group, and an ethyl group. 7 and / or R 8 When a plurality of are present, they may be the same or different. m is an integer of 0 to 10. n is an integer of 0 to 2.

[0038] Specific examples of the (meth)acrylic acid ester monomer having an alkoxysilyl group include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0039] The number of alkoxysilyl groups introduced into the (meth)acrylic copolymer is more than 2.0 on average, preferably 2.2 or more, more preferably 2.6 or more, even more preferably 3.0 or more, and particularly preferably 3.4 or more, in the whole molecule.The upper limit of the number of alkoxysilyl groups introduced into the (meth)acrylic copolymer is preferably 10.0 or less, more preferably 8.0 or less, even more preferably 6.0 or less, and particularly preferably 5.0 or less.When the number of alkoxysilyl groups is within the above range, a curable composition and a cured product with good physical properties can be obtained.

[0040] [2.1.3. Physical properties of (meth)acrylic copolymers] In one embodiment, the lower limit of the number average molecular weight of the (meth)acrylic copolymer is preferably 2,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more. The upper limit of the number average molecular weight of the (meth)acrylic copolymer is preferably 50,000 or less, more preferably 30,000 or less, and even more preferably 20,000 or less. When the number average molecular weight of the (meth)acrylic copolymer is in the above range, the viscosity of the curable composition does not become too high, and sufficient workability can be ensured.

[0041] In one embodiment, the molecular weight distribution of the (meth)acrylic copolymer is 1.8 or less, preferably 1.5 or less, 1.4 or less, 1.3 or less, or 1.2 or less. If the molecular weight distribution is within the above range, the viscosity of the polymer tends to decrease and the workability tends to improve. The molecular weight distribution is a value given by "weight average molecular weight ÷ number average molecular weight".

[0042] The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). For GPC measurement, chloroform is used as the mobile phase and a polystyrene gel column is used as the stationary phase. The molecular weight obtained by measurement is the molecular weight converted into standard polystyrene.

[0043] [2.1.4. Method for producing (meth)acrylic copolymer] The polymerization method of the (meth)acrylic copolymer is not particularly limited, and known polymerization methods can be used (radical polymerization method, cationic polymerization method, anionic polymerization method, etc.). The polymerization method called SGO (Solid Grade Oligomer; high temperature continuous bulk polymerization) is preferred because it is a method that can obtain a (meth)acrylic copolymer without using a polymerization solvent, a polymerization initiator, a chain transfer agent, etc. A living polymerization method is preferred because it can introduce a functional group near the end of the polymer molecule and can synthesize a (meth)acrylic copolymer with a small molecular weight distribution. Examples of living polymerization methods include living radical polymerization method, living cationic polymerization method, and living anionic polymerization method, and among them, living radical polymerization method is suitable for polymerization of a (meth)acrylic monomer. Examples of living radical polymerization methods include the following. Atom Transfer Radical Polymerization (ATRP) (see J. Am. Chem. Soc. 1995, 117, 5614; Macromolecules. 1995, 28, 1721) Single Electron Transfer Polymerization (SET-LRP (see J. Am. Chem. Soc. 2006, 128, 14156; JPSChem 2007, 45, 1607)) Reversible Chain Transfer Catalyzed Polymerization (RTCP) (see "Living Radical Polymerization Controlled by Organic Catalysts" Polymer Journal Vol. 68, 223-231 (2011); JP Patent Publication No. 2014-111798) Reversible addition-fragmentation chain transfer polymerization (RAFT polymerization) Nitroxy radical method (NMP method) Polymerization using organotellurium compounds (TERP method) · Polymerization method using organoantimony compounds (SBRP method) Polymerization method using organobismuth compounds (BIRP method) -Iodine transfer polymerization method

[0044] An example of a method for introducing a silyl group into a (meth)acrylic copolymer is the method described in JP 2018-162394 A. The method disclosed in the document introduces a silyl group into a (meth)acrylic copolymer by copolymerizing a (meth)acrylic acid ester monomer and a silyl group-containing (meth)acrylic acid ester monomer. More specifically, a silyl group is introduced near the end of a (meth)acrylic copolymer molecule by controlling the input amount of a silyl group-containing (meth)acrylic acid ester monomer according to the progress stage of living polymerization. The silyl group-containing (meth)acrylic copolymer obtained by these methods has a silyl group locally at or near the end of the molecule. The effect of reducing the surface tack of the cured product is prominently exhibited in a (meth)acrylic copolymer into which a silyl group has been introduced by such a method.

[0045] [2.2.(B) Oxygen curing substance] In this specification, the term "oxygen curable substance" refers to a compound having an unsaturated group that can be crosslinked and cured by oxygen in the air. The cured product obtained from the curable composition containing the oxygen curable substance tends to have reduced surface tackiness, but by adopting the production method according to one embodiment of the present invention, the surface tackiness can be further reduced. A typical oxygen curable substance cures, for example, by leaving it in air indoors for one day.

[0046] In one embodiment, the oxygen curing substance is preferably a compound having multiple double bonds in the molecule. The number of double bonds that the oxygen curing substance has may be 2 or more, 3 or more, or 4 or more.

[0047] Examples of oxygen-curable substances include drying oils (tung oil, linseed oil, etc.); various alkyd resins obtained by modifying drying oils; substances obtained by modifying acrylic polymers, epoxy resins, silicone resins, etc. with drying oils; 1,2-polybutadiene; 1,4-polybutadiene; polymers or copolymers of C5-C8 dienes; various modified products of polymers or copolymers of C5-C8 dienes (malein modified products, boiled oil modified products, etc.). Among the above, tung oil, liquid diene polymers, and modified products thereof are preferred.

[0048] The content of the oxygen-curable substance is preferably 0.01 to 30 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0049] [2.3.(C) Amines] The amine promotes hydrolysis and condensation of the silyl group (alkoxysilyl group) contained in the polymer, thereby crosslinking the polymers.

[0050] Specific examples of amines include amines (octylamine, 2-ethylhexylamine, laurylamine, stearylamine, etc.); nitrogen-containing heterocyclic compounds (pyridine, 1,8-diazabicyclo[5,4,0]undecene-7 (DBU), 1,5-diazabicyclo[4,3,0]nonene-5 (DBN)); guanidines (guanidine, phenylguanidine, diphenylguanidine, etc.); biguanides (butylbiguanide, 1-o-tolylbiguanide, 1-phenylbiguanide, etc.); amino group-containing silane coupling agents; and ketimine compounds.

[0051] The content of the amine is preferably 0.01 to 10 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0052] [2.4.(D) Curing catalyst] (D) An example of the curing catalyst is a tin-based curing catalyst. Specific examples of the tin-based curing catalyst include dialkyltin carboxylates (dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diethylhexanolate, dibutyltin dioctate, dibutyltin dimethyl maleate, dibutyltin diethyl maleate, dibutyltin dibutyl maleate, dibutyltin diisooctyl maleate, dibutyltin ditridecyl maleate, dibutyltin dibenzyl maleate, dibutyltin maleate, dioctyltin diacetate, dioctyltin distearate, dioctyltin dilaurate, dioctyltin diethyl maleate, dioctyltin diisooctyl maleate, etc.); dialkyltin oxides (dibutyltin oxide, dioctyltin oxide, a mixture of dibutyltin oxide and a phthalate ester, etc.); tetravalent tin compounds (dialkyltin oxide, dialkyltin oxide, dialkyltin oxide, dioctyltin oxide, a mixture of dibutyltin oxide and a phthalate ester, etc.); Reaction products of tin diacetate, etc.) with low molecular weight silicon compounds having alkoxysilyl groups (tetraethoxysilane, methyltriethoxysilane, diphenyldimethoxysilane, phenyltrimethoxysilane, etc.); divalent tin compounds (tin octylate, tin naphthenate, tin stearate, etc.); monoalkyltin compounds (monobutyltin compounds (monobutyltin tris-octoate, monobutyltin triisopropoxide, etc.), monooctyltin compounds, etc.); chelate compounds (dibutyltin bisacetylacetonate, dioctyltin bisacetylcetonate, dibutyltin bisethylacetonate, dioctyltin bisethylacetonate, etc.); tin alcoholates (dibutyltin dimethylate, dibutyltin diethylate, dioctyltin dimethylate, dioctyltin diethylate, etc.).

[0053] Among these, chelate compounds (such as dibutyltin bisacetylacetonate) and tin alcoholates are preferred because they have high activity as silanol condensation catalysts, and dibutyltin dilaurate is preferred because it causes little coloring when added to a curable composition, is inexpensive, and is easily available.

[0054] The content of the curing catalyst is preferably 0.1 to 5 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0055] [2.5. (E) Polyoxyalkylene polymer having silyl group] The curable composition obtained by the production method according to one embodiment of the present invention may contain, as an optional component, (E) a polyoxyalkylene polymer having a silyl group.

[0056] [2.5.1. Main chain of polyoxyalkylene polymer] The molecular structure of the polyoxyalkylene polymer may be linear or branched. It may also be a mixture of molecules having these structures. Among these, the main chain derived from one or more selected from the group consisting of polyoxypropylene diol and polyoxypropylene triol is particularly preferred.

[0057] Examples of the main chain structure of the polyoxyalkylene polymer include a structure represented by the following general formula: 9 is a divalent alkylene group. -R 9 -O-

[0058] The structure represented by formula (3) preferably accounts for 50% by weight or more of the total weight of the polyoxyalkylene polymer, more preferably 70% by weight or more, and even more preferably 90% by weight or more.

[0059] R 9 The structure of R is not particularly limited as long as it is a divalent alkylene group. 9 is preferably an alkylene group having 1 to 14 carbon atoms, and more preferably a linear or branched alkylene group having 2 to 4 carbon atoms.

[0060] Specific examples of the repeating unit represented by formula (3) include -CH 2 O-, -CH2 CH 2 O-, -CH 2 CH(CH 3 )O-, -CH 2 CH(C 2 H 5 )O-, -CH 2 C(CH 3 ) 2 O-, -CH 2 CH 2 CH 2 CH 2 Among these, the main chain of the polyoxyalkylene polymer is -CH 2 CH(CH 3 )O- The polyoxyalkylene polymer may contain a urethane bond or a urea bond in the main chain structure.

[0061] As the polyoxyalkylene polymer, commercially available products can be used. Examples of commercially available polyoxyalkylene polymers include Kaneka MS Polymer (registered trademark) S810, S257, S327 (all Kaneka Corporation); Silyl (registered trademark) SAX220, SAT400, SAX510, SAX520, SAX580, SAX750, SAT145 (all Kaneka Corporation); Exestar (registered trademark) ES-S2410, ES-S2420, ES-S3630 (all AGC Corporation); and HMS-1603, HMS-1207 (all Hua Ma Technology).

[0062] [2.5.2. Silyl groups of polyoxyalkylene polymers] The structure of the silyl group contained in the polyoxyalkylene polymer is not particularly limited. The silyl group contained in the polyoxyalkylene polymer may be the alkoxysilyl group contained in the (meth)acrylic copolymer described in Section [1.1.2.].

[0063] In one embodiment, the structure of the silyl group contained in the polyoxyalkylene polymer is represented by the following formula. -Si(R 3 ) 3-a (X)a

[0064] In the formula, one silyl group is R 3 When multiple R are included, they may be the same or different. 3 R represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms. 3 When R is substituted, it may be substituted with a heteroatom-containing group. When multiple silyl groups are present, R 3 may be different for each silyl group. 3 Examples of X include an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms. When one silyl group contains a plurality of Xs, they may be the same or different. X represents a hydroxyl group or a hydrolyzable group. When a plurality of silyl groups are present, X may be different for each silyl group. An example of the hydrolyzable group is an alkoxy group. a is 1, 2, or 3.

[0065] Examples of the silyl group contained in the polyoxyalkylene polymer include a dimethoxysilyl group, a trimethoxysilyl group, a diethoxysilyl group, a triethoxysilyl group, a triisopropoxysilyl group, a dimethoxymethylsilyl group, a diethoxymethylsilyl group, and a diisopropoxymethylsilyl group.

[0066] The number of silyl groups introduced into the polyoxyalkylene polymer is preferably more than 1.2 per molecule, more preferably 1.2 to 4.0, and even more preferably 1.5 to 2.5. When the number of silyl groups is within the above range, good curability can be imparted to the curable composition.

[0067] In addition to the above, it is also possible to use a polyalkylene polymer having only one silyl group at the end. When used in combination with the above polymer, it is possible to replace the plasticizer component. Furthermore, it is possible to use a polyalkylene polymer obtained by the synthesis method described in JP 2021-75722 A.

[0068] The silyl group of the polyoxyalkylene polymer is preferably located at at least one end of the molecule, and more preferably located at both ends of the molecule. If the silyl group is located at the end of the molecule, good elongation can be imparted to the cured product.

[0069] [2.5.3. Other physical properties of polyoxyalkylene polymers] The lower limit of the number average molecular weight of the polyoxyalkylene polymer is not particularly limited, and is preferably 3,000 or more, more preferably 10,000 or more, and even more preferably 20,000 or more. The upper limit of the number average molecular weight of the polyoxyalkylene polymer is preferably 70,000 or less, and more preferably 50,000 or less. By using a high molecular weight polymer having a number average molecular weight of 20,000 or more as the polyoxyalkylene polymer, the elongation of the cured product can be improved.

[0070] The molecular weight distribution of the polyoxyalkylene polymer is preferably 1.6 or less, more preferably 1.5 or less, and further preferably 1.2 or less. If the molecular weight distribution is too large, the viscosity of the curable composition increases, and the workability tends to decrease.

[0071] Such a polyoxyalkylene polymer can be obtained by the method described in

[0011] to

[0058] of JP2021-55010A.

[0072] The lower limit of the content of the polyoxyalkylene polymer is preferably 5 parts by weight or more, more preferably 30 parts by weight or more, and even more preferably 40 parts by weight or more, when the content of the (meth)acrylic copolymer having an alkoxysilyl group (A) is 100 parts by weight. The upper limit of the content of the polyoxyalkylene polymer is preferably 300 parts by weight or less, more preferably 280 parts by weight or less, and even more preferably 250 parts by weight or less, when the content of the (meth)acrylic copolymer having an alkoxysilyl group (A) is 100 parts by weight. If the content ratio of the (meth)acrylic copolymer and the polyoxyalkylene polymer is within the above range, a cured product with excellent weather resistance can be obtained. In order to ensure weather resistance for a longer period of time, it is preferable to contain more (meth)acrylic copolymer than polyoxyalkylene polymer.

[0073] [2.6. Other ingredients] The curable composition may contain various additives in addition to the above-mentioned components. By incorporating these additives, various physical properties of the curable composition and the cured product can be adjusted. Examples of additives include the following. These additives may be used alone or in combination of two or more. These additives may be added in one or more of steps (1) to (3), or may be added before step (1) or after step (3).

[0074] (Adhesion promoter) The curable composition may contain an adhesion promoter. By adding an adhesion promoter, the risk of the sealant peeling off from the adherend such as a siding board can be reduced (this peeling occurs when the joint width changes due to an external force). In addition, there may be cases where it is not necessary to use a primer to improve adhesion. In this case, simplification of the construction work is expected.

[0075] An example of an adhesion promoter is a silane coupling agent. Specific examples of silane coupling agents include isocyanate group-containing silanes (γ-isocyanate propyl trimethoxysilane, γ-isocyanate propyl triethoxysilane, γ-isocyanate propyl methyl diethoxysilane, γ-isocyanate propyl methyl dimethoxysilane, etc.); amino group-containing silanes (γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl methyl dimethoxysilane, γ-aminopropyl methyl diethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl diethoxysilane, γ-ureidopropyl trimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, N-benzyl-γ-aminopropyl trimethoxysilane, silane, N-vinylbenzyl-γ-aminopropyltriethoxysilane, etc.); mercapto group-containing silanes (γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropylmethyldiethoxysilane, etc.); carboxysilanes (β-carboxyethyltriethoxysilane, β-carboxyethylphenylbis(2-methoxyethoxy)silane, N-(β-carboxymethyl)aminoethyl-γ-aminopropyltrimethoxysilane, etc.); vinyl-type unsaturated group-containing silanes (vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloyloxypropylmethyldimethoxysilane, γ-acroyloxypropylmethyltriethoxysilane, etc.); halogen-containing silanes (γ-chloropropyltrimethoxysilane, etc.); isocyanurate silanes (tris(trimethoxysilyl)isocyanurate, etc.).In addition, derivatives obtained by modifying silane coupling agents, such as amino-modified silyl polymers, silylated amino polymers, unsaturated aminosilane complexes, phenylamino long-chain alkylsilanes, aminosilylated silicones, and silylated polyesters, can also be used as silane coupling agents.

[0076] The content of the adhesion promoter is preferably 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0077] (filling material) The curable composition may contain a filler. Examples of the filler include wood flour, reinforcing fillers (pulp, cotton chips, asbestos, mica, walnut shell powder, rice husk powder, graphite, white clay, silica (fumed silica, precipitated silica, crystalline silica, fused silica, dolomite, silicic anhydride, hydrated silicic acid, etc.), carbon black, etc.), fillers (heavy calcium carbonate, colloidal calcium carbonate, magnesium carbonate, diatomaceous earth, calcined clay, clay, talc, titanium oxide, bentonite, organic bentonite, ferric oxide, red iron oxide, fine aluminum powder, flint powder, zinc oxide, activated zinc oxide, zinc powder, zinc carbonate, shirasu balloon, etc.), and fibrous fillers (asbestos, glass fiber and glass filament, carbon fiber, Kevlar fiber, polyethylene fiber, etc.).

[0078] The content of the filler is preferably 5 to 5,000 parts by weight, more preferably 10 to 2,500 parts by weight, and particularly preferably 15 to 1,500 parts by weight, relative to 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0079] (Plasticizer) The curable composition may contain a plasticizer. The use of a plasticizer in combination with a filler increases the elongation of the cured product and allows the incorporation of a large amount of filler.

[0080] Examples of plasticizers include phthalates (dibutyl phthalate, diheptyl phthalate, di(2-ethylhexyl) phthalate, diisodecyl phthalate, butyl benzyl phthalate, etc.); non-aromatic dibasic acid esters (dioctyl adipate, dioctyl sebacate, dibutyl sebacate, isodecyl succinate, etc.); aliphatic esters (butyl oleate, methyl acetylricinoleate, etc.); esters of polyalkylene glycols (diethylene glycol dibenzoate, triethylene glycol dibenzoate, pentaerythritol esters, etc.); phosphate esters (tricresyl phosphate, tributyl phosphate, etc.); trimellitic acid esters, polystyrenes (polystyrene, poly-α-methylstyrene, etc.); polybutadiene; polybutene; polyisobutylene; butadiene. Examples of suitable plasticizers include diene-acrylonitrile, polychloroprene, chlorinated paraffins, hydrocarbon oils (alkyldiphenyls, partially hydrogenated terphenyls, etc.), process oils, polyethers (polyether polyols (polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc.), and derivatives in which the hydroxyl groups of polyether polyols are converted to ester groups, ether groups, etc.), polyester plasticizers obtained from dibasic acids and dihydric alcohols (polyesters obtained from sebacic acid, adipic acid, azelaic acid, phthalic acid, etc., and ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, etc.), and vinyl polymers (obtained by polymerizing vinyl monomers such as acrylic plasticizers by various methods).

[0081] Acrylic plasticizers can be produced by high-temperature continuous polymerization without using solvents and chain transfer agents (see U.S. Pat. No. 4,414,370, JP-A-59-6207, JP-B-5-58005, JP-A-1-313522, and U.S. Pat. No. 5,010,166). Specific examples of acrylic plasticizers include ARUFON UP-1000, UP-1020, and UP-1110 (all from Toagosei Co., Ltd.), JDX-P1000, JDX-P1010, and JDX-P1020 (all from Johnson Polymer Co., Ltd.).

[0082] The content of the plasticizer is preferably 5 to 800 parts by weight, more preferably 10 to 600 parts by weight, and even more preferably 10 to 500 parts by weight, relative to 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0083] (Physical property adjuster) The curable composition may contain a physical property modifier that adjusts the tensile properties of the cured product. By using the physical property modifier, it is possible to increase the hardness of the cured product, or conversely, to decrease the hardness of the cured product and increase the elongation.

[0084] Examples of physical property adjusters include alkylalkoxysilanes (methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, n-propyltrimethoxysilane, etc.); alkylisopropenoxysilanes (dimethyldiisopropenoxysilane, methyltriisopropenoxysilane, etc.); alkoxysilanes having functional groups (vinyldimethylmethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)aminopropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, etc.); silicone varnishes; and polysiloxanes.

[0085] The content of the physical property adjusting agent is preferably 0.1 to 80 parts by weight, and more preferably 0.1 to 50 parts by weight, per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0086] (Thixotropic agent (anti-sagging agent)) The curable composition may contain a thixotropic agent (anti-sagging agent) to prevent sagging and improve workability.

[0087] Examples of the thixotropic agent include polyamide waxes; hydrogenated castor oil derivatives; and metal soaps (calcium stearate, aluminum stearate, barium stearate, etc.).

[0088] The content of the thixotropy-imparting agent is preferably 0.1 to 50 parts by weight, and more preferably 0.2 to 25 parts by weight, relative to 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0089] (light curing substance) The curable composition may contain a photocurable substance. A photocurable substance is a substance that undergoes a chemical change in a short time by the action of light, resulting in a change in physical properties (such as curing). By including a photocurable substance, the tackiness (residual tack) of the surface of the cured product can be reduced. A typical photocurable substance can be cured by leaving it at room temperature for one day, for example, in a sunny position indoors (such as near a window). Many photocurable substances are known, such as organic monomers, oligomers, resins, and compositions containing these, and the types are not particularly limited. Examples of photocurable substances include unsaturated acrylic compounds, polyvinyl cinnamates, and azido resins.

[0090] Specific examples of unsaturated acrylic compounds include (meth)acrylic acid esters of low molecular weight alcohols (ethylene glycol, glycerin, trimethylolpropane, pentaerythritol, neopentyl alcohol, etc.); (meth)acrylic acid esters of alcohols obtained by modifying acids (bisphenol A, isocyanuric acid) or low molecular weight alcohols with ethylene oxide, propylene oxide, etc.; (meth)acrylic acid esters (polyether polyols whose main chain is polyether and has hydroxyl groups at the terminals, and vinyl monomers radically polymerized in polyols whose main chain is polyether). polymer polyols obtained by reacting an epoxy resin (such as bisphenol A type or novolak type) with (meth)acrylic acid, polyester polyols having a polyester main chain and hydroxyl groups at the terminals, and polyols having a vinyl or (meth)acrylic copolymer main chain and hydroxyl groups in the main chain; epoxy acrylate oligomers obtained by reacting an epoxy resin (such as bisphenol A type or novolak type) with (meth)acrylic acid; and urethane acrylate oligomers having urethane bonds and (meth)acrylic groups in the molecular chain obtained by reacting a polyol, a polyisocyanate, a hydroxyl group-containing (meth)acrylate, etc.

[0091] The content of the photocurable substance is preferably 0.01 to 30 parts by weight per 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0092] (Antioxidants and Light Stabilizers) The curable composition may contain an antioxidant and / or a light stabilizer. Various antioxidants and light stabilizers are known. For example, the substances described in [Kenichi Saruwatari et al., "Antioxidant Handbook," Taiseisha, 1976] and [Zenjiro Osawa, editor, "Deterioration and Stabilization of Polymer Materials," CMC, 1990, pp. 235-242] can be mentioned.

[0093] Examples of the antioxidant include thioether-based antioxidants such as ADK STAB PEP-36 and ADK STAB AO-23 (all manufactured by ADEKA Corporation); phosphorus-based antioxidants such as Irgafos38, Irgafos168, and IrgafosP-EPQ (all manufactured by Ciba Specialty Chemicals); and hindered phenol-based antioxidants. Among the above, hindered phenol-based antioxidants are preferred.

[0094] Specific examples of hindered phenol-based antioxidants include 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-ethylphenol, mono (or di or tri) (α-methylbenzyl)phenol, 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), and 2,5-di-t-butylhydroquinone. , 2,5-di-t-amylhydroquinone, triethylene glycol-bis-[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylene 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-t-butyl-4-hydroxybenzyl)propionate, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 3,5-di-t-butyl-4-hydroxy-benzylphosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-t-butyl-4-hydroxybenzyl)propionate ethyl benzylphosphonate) calcium, tris-(3,5-di-t-butyl-4-hydroxybenzyl) isocyanurate, 2,4-bis[(octylthio)methyl]o-cresol, N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl]hydrazine, tris(2,4-di-t-butylphenyl)phosphite, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3,5-di-t-amyl-2-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)-benzotriazole, methyl-3-[3-t-bu ethyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate-polyethylene glycol (molecular weight about 300) condensate, hydroxyphenylbenzotriazole derivatives, 2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butylmalonic acid bis(1,2,2,6,6-pentamethyl-4-piperidyl), 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate.

[0095] Examples of commercially available antioxidants include Nocrac 200, Nocrac M-17, Nocrac SP, Nocrac SP-N, Nocrac NS-5, Nocrac NS-6, Nocrac NS-30, Nocrac 300, Nocrac NS-7, and Nocrac DAH (all manufactured by Ouchi Shinko Chemical Industry Co., Ltd.); ADK STAB AO-30, ADK STAB AO-40, ADK STAB AO-50, ADK STAB AO-60, ADK STAB AO-616, ADK STAB AO-635, ADK STAB AO-658, ADK STAB AO-80, ADK STAB AO-15, ADK STAB AO-18, ADK STAB 328, and ADK STAB AO-37 (all manufactured by ADEKA Corporation); IRGANOX-245, IRGANOX-259, IRGANOX-565, IRGANOX-1010, IRGANOX-1024, IRGANOX-1035, IRGANOX-1076, IRGANOX-1081, IRGANOX-1098, IRGANOX-1222, IRGANOX-1330, IRGANOX-1425WL (all manufactured by Chiba Specialty Chemicals); Sumilizer GM, Sumilizer GA-80, Sumilizer GS (all manufactured by Sumitomo Chemical Co., Ltd.).

[0096] Examples of light stabilizers include ultraviolet absorbers (benzotriazole compounds such as Tinuvin P, Tinuvin 234, Tinuvin 320, Tinuvin 326, Tinuvin 327, Tinuvin 329, and Tinuvin 213 (all manufactured by Ciba Specialty Chemicals); triazine light stabilizers such as Tinuvin 1577; benzophenone compounds such as CHIMASSORB81; benzoate compounds such as Tinuvin 120 (manufactured by Ciba Specialty Chemicals); and hindered amine compounds). Of the above, hindered amine compounds are preferred.

[0097] Specific examples of the hindered amine compound include dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}], N,N'-bis(3aminopropyl)ethylenediamine-2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino]-6-chloro-1,3,5-triazine condensate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, and bis(2,2,6,6-tetramethyl-4-piperidinyl)succinate.

[0098] Examples of commercially available light stabilizers include Tinuvin 622LD, Tinuvin 144, CHIMASSORB944LD, and CHIMASSORB119FL (all manufactured by Chiba Specialty Chemicals), Adeka STAB LA-52, Adeka STAB LA-57, Adeka STAB LA-62, Adeka STAB LA-67, Adeka STAB LA-63, Adeka STAB LA-68, Adeka STAB LA-82, and Adeka STAB LA-87 (manufactured by ADEKA Corporation); Sanol LS-770, Sanol LS-765, Sanol LS-292, Sanol LS-2626, Sanol LS-1114, Sanol LS-744, and Sanol LS-440 (manufactured by Chiba Specialty Chemicals).

[0099] An antioxidant and a light stabilizer may be used in combination. By using them in combination, the effect of each agent may be further improved, and the heat resistance, weather resistance, etc. of the cured product may be improved. For example, in order to improve weather resistance, an ultraviolet absorber and a hindered amine compound (HALS) may be combined. This combination is preferable because it can further improve the effect of each agent.

[0100] The content of the antioxidant and / or light stabilizer is preferably 0.1 to 20 parts by weight, based on 100 parts by weight of the total amount of (A) the (meth)acrylic copolymer having an alkoxysilyl group and (E) the polyoxyalkylene polymer having a silyl group.

[0101] [3. Summary] The present invention includes the following aspects. <1> A method for producing a curable composition, comprising the following steps (1) to (3): Step (1): (A) mixing a (meth)acrylic copolymer having an alkoxysilyl group with (B) an oxygen-curable substance; Step (2): adding an amine (C) to the mixture obtained in step (1); Step (3): adding a curing catalyst (D) to the mixture obtained in step (2); The (A) (meth)acrylic copolymer having an alkoxysilyl group has a molecular weight distribution (Mw / Mn) of 1.8 or less, The (A) (meth)acrylic copolymer having an alkoxysilyl group has an XY diblock structure having an X block and a Y block or an XYX triblock structure in the molecule, the number of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is on average more than 2.0 per molecule of the (A) (meth)acrylic copolymer having an alkoxysilyl group, the content of a repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block; Manufacturing method. <2> The oxygen-curable substance (B) is a compound having multiple double bonds in the molecule. <1> A method for producing the curable composition according to claim 1. <3> The (A) (meth)acrylic copolymer having an alkoxysilyl group is R 1 CH=CHCOOR 2 Contains 1% by weight or more of repeating units derived from In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 is a group having 9 or more carbon atoms, <1> or <2> A method for producing the curable composition according to claim 1. <4> The number average molecular weight of the (A) (meth)acrylic copolymer having an alkoxysilyl group is 2,000 or more and 50,000 or less. <1> ~ <3> 13. A method for producing the curable composition according to any one of claims 1 to 12. <5> In the above step (1), (E) a polyoxyalkylene polymer having a silyl group is further mixed. <1> ~ <4> 13. A method for producing the curable composition according to any one of claims 1 to 12. <6> The silyl group of the (E) polyoxyalkylene polymer having a silyl group is represented by the formula: -Si(R 3 ) 3-a (X) a Represented by <5> A method for producing the curable composition according to claim 1, During the ceremony, R 3 represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms; R 3 may be substituted with a heteroatom-containing group; R in one silyl group 3 When multiple are included, they may be the same or different; R 3 may be different for each silyl group; X represents a hydroxyl group or a hydrolyzable group; When one silyl group contains a plurality of X's, they may be the same or different. X may be different for each silyl group; a is 1, 2 or 3. <7> The number average molecular weight of the (E) polyoxyalkylene polymer having a silyl group is 3,000 or more and 50,000 or less. <5> or <6> A method for producing the curable composition according to claim 1. <8> <1> ~ <7> preparing a curable composition by any one of the methods for producing the curable composition according to any one of the above; curing the curable composition; The method for producing a cured product comprising the steps of: EXAMPLES

[0102] [Measurement method] [Number average molecular weight and weight average molecular weight] The following devices were used to measure the number average molecular weight and the weight average molecular weight. The measured values ​​are polystyrene-equivalent molecular weights. Liquid delivery system: HLC-8120GPC (Tosoh Corporation) Column: TSK-GEL H type (Tosoh Corporation) Solvent: THF

[0103] [Molecular weight distribution] The molecular weight distribution was calculated by dividing the weight average molecular weight by the number average molecular weight.

[0104] [Terminal silyl group introduction rate] 1 The introduction rate of terminal silyl groups was calculated from the results of H-NMR measurement. 1 The following equipment was used for H-NMR measurements. Measuring instrument: JNM-LA400 (JEOL Ltd.) Solvent: CDCl 3

[0105] [Surface tack] The surface of the cured product was touched with a finger to evaluate the surface tackiness. The evaluation criteria were as follows: ++: No tack felt at all. +: Almost no tack felt. -: Feels a strong tack.

[0106] [Tensile properties] The tensile properties were measured by cutting No. 3 dumbbell-shaped test pieces from the cured products in accordance with JIS K 6251. The tensile properties were measured at 23°C and 55% RH using an autograph. The evaluation items were the stress at 100% elongation, the stress at break, and the elongation at break.

[0107] [Tear strength] A crescent-shaped test piece was obtained from the cured product, and the tear strength was measured in accordance with JIS K 6252. The tear strength was measured using an autograph at 23°C and 55% RH.

[0108] 〔material〕 The following materials were used: (A) (Meth)acrylic copolymer having an alkoxysilyl group Silyl group-containing (meth)acrylic copolymer (A-1) obtained in Production Example 1 ●(B) Oxygen curing substance ·Tung oil (drying oil) ●(C) Amine Laurylamine ●(D) Curing catalyst Stannous octoate (E) Polyoxyalkylene polymer having a silyl group Silyl group-containing polyoxyalkylene polymer (E-1) obtained in Production Example 2 (Meth)acrylic copolymers with alkoxysilyl groups that do not satisfy the conditions (Meth)acrylic copolymer (A'-1) obtained in Comparative Production Example 1

[0109] [Production Example 1: Synthesis of silyl group-containing (meth)acrylic copolymer (A-1)] A silyl group-containing (meth)acrylic copolymer (A-1) was synthesized by the following procedure. This copolymer satisfies the requirements for (A) a (meth)acrylic copolymer having an alkoxysilyl group. [Preparation] 1. A 2000 mL three-neck flask was prepared. 108 g of ethyl acrylate, 707 g of n-butyl acrylate, and 186 g of octadecyl acrylate were charged into the flask and mixed. This mixture is referred to as "(meth)acrylic acid ester monomer mixture." 2. Prepare another stirring vessel. Add 52.7 mg of copper(II) bromide (CuBr 2 ), 54.4 mg of hexamethyltris(2-aminoethyl)amine (Me 6 TREN) and 1.82 g of methanol were charged in a stirring vessel and stirred under a nitrogen gas flow until a homogeneous solution was obtained. This homogeneous solution is referred to as the "copper solution." The copper contained in the copper solution was equivalent to 15 ppm relative to the total amount of the (meth)acrylic acid ester monomer mixture. 3. Another stirring vessel was prepared. 30.8 mL of methanol, 1.0 g of ascorbic acid, and 1.6 mL of triethylamine were charged into the stirring vessel and stirred under a nitrogen stream to obtain a homogeneous solution. This homogeneous solution is called "ascorbic acid solution." [1st step] 4. 5.60g of ethyl α-bromobutyrate (initiator; 0.029 mol), 20% by weight of the total amount of (meth)acrylic acid ester monomer mixture, 10g of 3-methacryloxypropylmethyldimethoxysilane (0.045 mol; 1.5 molar equivalent to the initiator), 107.68g of methanol, and the total amount of copper solution were added to the stirrer, and stirred for 30 minutes under a nitrogen stream to obtain a homogeneous solution. The stirrer used at this time was a stirrer with a jacket temperature control, and the jacket temperature was set to 45°C. 5. When the temperature in the polymerization system reached 40°C or higher, the ascorbic acid solution was continuously dripped to start the polymerization reaction. The dripping rate of the ascorbic acid solution was set to a rate at which 144 mg of ascorbic acid was added to the polymerization system per hour. 6. The temperature in the polymerization system was monitored and it rose as soon as the dropping of ascorbic acid started, reached a maximum temperature, and then gradually decreased. When the temperature difference between the temperature in the polymerization system and the jacket temperature reached 1°C, a small amount of the reaction solution in the polymerization system was sampled and analyzed by gas chromatography. As a result, 90% by weight of the (meth)acrylic acid ester monomer mixture initially charged had been consumed. [Second process] 7. The remaining (meth)acrylic acid ester monomer mixture that was not added in the first step (80% by weight of the total amount) was continuously added dropwise to the polymerization system over a period of 90 minutes. The ascorbic acid solution was added dropwise at a rate of 48 mg of ascorbic acid per hour to the polymerization system. Sampling was also carried out sequentially and analyzed by gas chromatography. The polymerization was continued until 88% by weight of the total (meth)acrylic acid ester monomer mixture added to the polymerization system was consumed. [3rd step] 8. 11 g of 3-methacryloxypropylmethyldimethoxysilane (0.049 mol; 1.6 molar equivalents relative to the initiator) was added to the polymerization system. The ascorbic acid solution was continuously added dropwise until 98% by weight of the total amount of the (meth)acrylic acid ester monomer mixture added to the polymerization system was consumed. Thereafter, the addition of the ascorbic acid solution was stopped to terminate the polymerization. 9. The jacket temperature was changed to 80°C, and the solvent was then volatilized. A diaphragm pump was used first, and then a vacuum pump was used. After volatilization was completed, the jacket temperature was cooled to 60°C or less. [purification] 10. 1000g of butyl acetate was added to a jacket temperature-controlled stirring device and mixed with the polymer after devolatilization until a homogeneous solution was obtained. An adsorbent was added to this homogeneous solution and stirred for 1 hour. As the adsorbent, 10g of Kyoward 500SH (Kyowa Chemical Industry Co., Ltd.) and 10g of Kyoward 700SEN-S (Kyowa Chemical Industry Co., Ltd.) were used. 11. After the stirring was completed, the mixture was filtered through a filter equipped with a bag filter cloth. This resulted in a clear polymer solution. 1.5 g of an antioxidant (Sumilizer GS; Sumitomo Chemical Co., Ltd.) was added to the solution and mixed until homogenous. Thereafter, the solvent was removed from the solution using a diaphragm pump first and then a vacuum pump. In this way, a (meth)acrylic copolymer (A-1) was obtained.

[0110] The (meth)acrylic copolymer (A-1) was an XYX type block copolymer, with a number average molecular weight of 5,5000, a molecular weight distribution of 1.11, and a number of silyl groups introduced per molecule of 2.1. The X block of the (meth)acrylic copolymer (A-1) had an average of 2.1 repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group per copolymer molecule. The Y block of the (meth)acrylic copolymer (A-1) had 1.1% by weight of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group (based on the weight of all repeating units contained in the Y block). The repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block were extremely small. Therefore, when calculated with two significant digits, the number of repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the entire molecule, and the number of repeating units derived from the (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the entire X block are both 2.1.

[0111] [Production Example 2: Synthesis of silyl group-containing polyoxyalkylene polymer (E-1)] A polyoxyalkylene polymer (E-1) having a methyldimethoxysilyl group introduced at the molecular terminal was synthesized according to the following procedure. 1. Propylene oxide was polymerized to obtain polypropylene oxide with a number average molecular weight of approximately 16,400. Polyoxypropylene triol was used as the initiator (molecular weight: approximately 3,000). Zinc hexacyanocobaltate glyme complex was used as the catalyst. The resulting polypropylene oxide has three terminals that are all hydroxyl groups. 2. 1.2 equivalents of NaOMe relative to the hydroxyl groups at the terminals of the polypropylene oxide molecule were added as a methanol solution. The methanol was distilled off. 3. Allyl chloride was added to convert the hydroxyl groups at the ends of the polypropylene oxide molecules to allyl groups, yielding crude allyl-terminated polypropylene oxide. 4. 100 parts by weight of unpurified allyl-terminated polypropylene oxide was mixed with 300 parts by weight of n-hexane and 300 parts by weight of water and stirred. Then, the water was removed by centrifugation. 5. The resulting solution was mixed with 300 parts by weight of water again and stirred. Then, the water was removed by centrifugation. 6. The n-hexane was removed by volatilization under reduced pressure to obtain purified allyl-terminated polypropylene oxide. 7. 1.80 parts by weight of methyldimethoxysilane was added to 100 parts by weight of the purified allyl-terminated polypropylene oxide, and the mixture was reacted at 90°C for 2 hours. An isopropanol solution of platinum vinylsiloxane complex (platinum content: 3 wt%) was used as the catalyst. The catalyst concentration in the system was 150 ppm. This produced a polyoxyalkylene polymer.

[0112] The polyoxyalkylene polymer (E-1) is a polypropylene oxide having a methyldimethoxysilyl group introduced at the end. The polyoxyalkylene polymer (E-1) had a number average molecular weight of 27,000, a molecular weight distribution of 1.2, and 2.0 silyl groups introduced per molecule.

[0113] Comparative Production Example 1: Synthesis of silyl group-containing (meth)acrylic copolymer (A'-1) A (meth)acrylic copolymer having methyldimethoxysilyl groups introduced at the molecular terminals was synthesized by the following procedure. The (meth)acrylic copolymer has alkoxysilyl groups located only at the molecular terminals and does not contain X blocks as a whole molecule, so it does not fall under the category of the (meth)acrylic copolymer having alkoxysilyl groups (A) in one embodiment of the present invention. 1. The inside of a stainless steel reaction vessel equipped with a stirrer was deoxidized. 7.7 g of cuprous bromide and 200 g of butyl acrylate were charged into the reaction vessel and stirred while heating. 2. 90g of acetonitrile and 17.6g of diethyl 2,5-dibromoadipate (initiator) were added to a reaction vessel and mixed. The temperature of the mixture was adjusted to about 80°C, and then pentamethyldiethylenetriamine was added to initiate the polymerization reaction. 3. 800 g of butyl acrylate was gradually added to the reaction vessel to proceed with the polymerization reaction. During the polymerization, pentamethyldiethylenetriamine was appropriately added to adjust the polymerization rate. The total amount of pentamethyldiethylenetriamine used during the polymerization was 1.4 g. During the polymerization reaction, the internal temperature of the reaction vessel was adjusted to about 80 to about 90°C. 4. When the monomer conversion rate (polymerization reaction rate) reached about 95% or more, the volatile matter was removed by devolatilization under reduced pressure to obtain a concentrated (meth)acrylic copolymer. 5. To the polymer concentrate obtained in step 4 was added 200 g of 1,7-octadiene, 260 g of acetonitrile, and 3.1 g of pentamethyldiethylenetriamine. 6. The mixture was heated and stirred for several hours while adjusting the internal temperature of the reaction vessel to about 80 to about 90° C. This caused the polymer terminals to react with 1,7-octadiene, and introduced alkenyl groups into the polymer terminals. 7. Acetonitrile and unreacted 1,7-octadiene were removed by volatilization under reduced pressure to obtain a concentrated polymer having alkenyl groups at its ends. 8. The concentrate obtained in step 7 was diluted with butyl acetate, and a filter aid and an adsorbent (Kyoward 700SEN and Kyoward 500SH, Kyowa Chemical Industry Co., Ltd.) were added. 9. The mixture obtained in step 8 was heated and stirred at about 80 to 100° C., and the solid components were filtered off. The filtrate was then concentrated to obtain a crude polymer. 10. A heat stabilizer (Sumilizer GS, Sumitomo Chemical Co., Ltd.) and an adsorbent (Kyoward 700SEN and Kyoward 500SH) were added to the crude polymer. 11. The temperature of the system was increased while removing volatilization under reduced pressure and heating with stirring, and the removal of volatilization under reduced pressure and heating with stirring were continued at about 170 to about 200° C. for several hours. 12. Adsorbents (Kyoward 700SEN and Kyoward 500SH) and butyl acetate in an amount about 10 times by weight relative to the crude polymer product were added, and the mixture was heated and stirred at about 170 to about 200° C. for several hours. 13. The treated liquid obtained in step 12 was further diluted with butyl acetate, and the adsorbent was filtered off. The filtrate was concentrated to obtain a polymer having alkenyl groups at both ends. 14. 500 g of the polymer obtained in step 13 was mixed with 7.7 g of methyldimethoxysilane, 2.5 g of methyl orthoformate, and 50 mg of platinum catalyst, and heated and stirred at about 100° C. for about 1 hour. As the platinum catalyst, an isopropanol solution of bis(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum complex catalyst was used. 15. Volatile components (unreacted methyldimethoxysilane, etc.) were distilled off under reduced pressure to obtain (meth)acrylic copolymer (A'-1) with methyldimethoxysilyl groups introduced at the molecular ends. (Meth)acrylic copolymer (A'-1) had a number average molecular weight of 27,000, a molecular weight distribution of 1.2, and the number of silyl groups introduced per molecule was 2.0.

[0114] [Examples 1 to 4, Comparative Examples 1 to 11] A cured product was prepared according to the following procedure. 1. Prepare each component in the amount (unit: g) shown in Table 1. 2. These ingredients were placed in a 150cc plastic cup and mixed using a spoon. The mixing order was one of the following two: ●Order A (A) A (meth)acrylic copolymer having an alkoxysilyl group or a (meth)acrylic copolymer not satisfying the condition (A') is mixed with (E) a polyoxyalkylene polymer having a silyl group. (B) The oxygen curing material is further added and mixed. Add more (C) amine and mix. (D) Add more curing catalyst and mix. ● Sequence B: (A) a (meth)acrylic copolymer having an alkoxysilyl group, (B) an oxygen curing substance, (C) an amine and (D) a curing catalyst are mixed simultaneously. 3. Using a planetary stirring and degassing device (ARE-310, Thinky Corporation), the mixture was stirred (1600 rpm x 90 seconds) and degassed (2200 rpm x 300 seconds) to obtain a curable composition. 4. The obtained curable composition was cured under conditions of 23°C and 50% RH to obtain a cured product.

[0115] 〔result〕 The results are shown in Table 1. [Table 1] JPEG2025029911000002.jpg159135

[0116] As can be seen from Table 1, the cured products of Examples 1 to 3 all had reduced surface tackiness, and mechanical strength was maintained at the same level or higher than that of the Comparative Examples (prior art). The cured products of Comparative Examples 1 to 7, which were produced using mixing order B, were unable to reduce surface tackiness. In particular, when comparing Example 1 and Comparative Example 7, it can be seen that even if cured products are produced using the same composition, the effect of reducing surface tackiness cannot be obtained unless mixing order A is adopted.

[0117] In addition, the surface tackiness of the curable compositions according to Comparative Examples 8 to 11, which contain a silyl group-containing (meth)acrylic copolymer that does not fall under the category of (A) a (meth)acrylic copolymer having an alkoxysilyl group, was not reduced even when the mixing order A was adopted. This result suggests that in order to reduce the surface tackiness of the cured product, it is important to adopt the mixing order A and to contain (A) a (meth)acrylic copolymer having an alkoxysilyl group. [Industrial Applicability]

[0118] The curable composition produced by the method according to one embodiment of the present invention can be suitably used for pressure sensitive adhesives, sealing materials, adhesives, mold release agents, vibration isolators, vibration dampers, soundproofing materials, foaming materials, paints, spray materials, etc.

Claims

1. A method for producing a curable composition, comprising the following steps (1) to (3): Step (1): A step of mixing (A) an alkoxysilyl group-containing (meth)acrylic copolymer and (B) an oxygen-curable substance; Step (2): adding an amine (C) to the mixture obtained in step (1); Step (3): adding a curing catalyst (D) to the mixture obtained in step (2); The (A) (meth)acrylic copolymer having an alkoxysilyl group has a molecular weight distribution (Mw / Mn) of 1.8 or less, The (A) (meth)acrylic copolymer having an alkoxysilyl group has an XY diblock structure having an X block and a Y block or an XYX triblock structure in the molecule, the number of repeating units derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the X block is on average more than 2.0 per molecule of the (A) (meth)acrylic copolymer having an alkoxysilyl group, the content of a repeating unit derived from a (meth)acrylic acid ester monomer having an alkoxysilyl group contained in the Y block is 0% by weight or more and less than 5% by weight based on the weight of all repeating units contained in the Y block; Manufacturing method.

2. The oxygen-curable substance (B) is a compound having a plurality of double bonds in the molecule. A method for producing the curable composition according to claim 1.

3. The (A) (meth)acrylic copolymer having an alkoxysilyl group is R 1 CH=CHCOOR 2 Contains 1% by weight or more of repeating units derived from In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is a group having 9 or more carbon atoms; A method for producing the curable composition according to claim 1.

4. The number average molecular weight of the (A) (meth)acrylic copolymer having an alkoxysilyl group is 2,000 or more and 50,000 or less. A method for producing the curable composition according to claim 1.

5. In the above step (1), (E) a polyoxyalkylene polymer having a silyl group is further mixed. A method for producing the curable composition according to claim 1.

6. The silyl group of the (E) polyoxyalkylene polymer having a silyl group is represented by the formula: -Si(R 3 ) 3-a (X) a Represented by A method for producing the curable composition according to claim 5, comprising: During the ceremony, R 3 represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms; R 3 may be substituted with a heteroatom-containing group; One silyl group has R 3 When multiple are included, they may be the same or different; R 3 may be different for each silyl group; X represents a hydroxyl group or a hydrolyzable group; When one silyl group contains a plurality of X's, they may be the same or different. X may be different for each silyl group; a is 1, 2 or 3.

7. The number average molecular weight of the (E) polyoxyalkylene polymer having a silyl group is 3,000 or more and 50,000 or less. A method for producing the curable composition according to claim 5.

8. A step of preparing a curable composition by the method according to any one of claims 1 to 7; curing the curable composition; The method for producing a cured product comprising the steps of:

Citation Information

Patent Citations

  • Curable composition

    JP2022049666A